2018
DOI: 10.1021/acs.jafc.7b05770
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene Supplementation Attenuates Oxidative Stress, Neuroinflammation, and Cognitive Impairment in Aged CD-1 Mice

Abstract: The carotenoid pigment lycopene (LYC) possesses several properties, including antioxidative, anti-inflammatory, and neuroprotective properties. This study examined the effects of dietary supplementation with LYC on age-induced cognitive impairment, and the potential underlying mechanisms. Behavioral tests revealed that chronic LYC supplementation alleviated age-associated memory loss and cognitive defects. Histological and immunofluorescence-staining results indicated that LYC treatment reversed age-associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 45 publications
0
48
1
Order By: Relevance
“…Thereafter, GSH‐PX and CAT can transform the resultant hydrogen peroxide into water, so as to protect cells from OS‐induced injury. In this study, our findings suggested that LYC increased the activities of antioxidant enzymes (including CAT, SOD, and GSH‐PX), which were the redox protectors and mitigated OS . Therefore, SOD, CAT, and GSH‐PX indirectly reflect the oxidation resistance.…”
Section: Discussionmentioning
confidence: 54%
“…Thereafter, GSH‐PX and CAT can transform the resultant hydrogen peroxide into water, so as to protect cells from OS‐induced injury. In this study, our findings suggested that LYC increased the activities of antioxidant enzymes (including CAT, SOD, and GSH‐PX), which were the redox protectors and mitigated OS . Therefore, SOD, CAT, and GSH‐PX indirectly reflect the oxidation resistance.…”
Section: Discussionmentioning
confidence: 54%
“…Furthermore, lycopene consumption considerably reduced age-related neuroinflammatory disorders by decreasing microgliosis (IBA-1), as well as down-regulating inflammatory mediators. In addition, a study revealed that lycopene down-regulates the Aβ1-42 accumulation in the brains of aged CD-1 mice [62]. Similarly, lycopene (0.03% w/w) has been found to inhibit the LPS (0.25 mg/kg)-induced memory loss in 3-month old male C57BL/6J mice by reducing Aβ accumulation, APP, reducing the expression of neuronal β-secretase beta-site amyloid precursor protein cleaving enzyme 1 (BACE1), and improving the α-secretase A disintegrin and metalloproteinase 10 (ADAM10) expressions.…”
Section: Neuroprotectivementioning
confidence: 99%
“…The quantitative real‐time PCR analysis was performed according to previous literature [ 16 ] with the gene‐specific primers shown in Table 1 . Ct values were normalized to glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH).…”
Section: Methodsmentioning
confidence: 99%